Recurrent persistent hypophosphatemia in a male‐to‐female transgender patient with anorexia nervosa: Case report. Issue 5 (28th March 2017) - Beaty, L.; Trees, N.; Mehler, P.
Abstract: Refeeding hypophosphatemia remains a serious and common complication during the early phases of nutritional rehabilitation and weight restoration for patients with anorexia nervosa. Typically, the risk of refeeding hypophosphatemia diminishes after the first 1–2 weeks of the refeeding process and thus, frequent monitoring serum phosphorus levels becomes less important as refeeding proceeds. Herein, we describe a case of persistent recurrent hypophosphatemia in a male‐to‐female transgender patient with severe anorexia nervosa. As transgender patients become increasingly seen in the realm of eating disorders, it is worth noting this phenomenon to mitigate adverse events.